2015
DOI: 10.1118/1.4918923
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning for radiotherapy with very high‐energy electron beams and comparison of VHEE and VMAT plans

Abstract: The authors have developed a treatment planning workflow for MC dose calculation of pencil beams and optimization for treatment planning of VHEE radiotherapy. The authors have demonstrated that VHEE plans resulted in similar or superior dose distributions for pediatric, lung, and prostate cases compared to clinical VMAT plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 23 publications
3
88
0
Order By: Relevance
“…The largest benefit for the 100 MeV VHEE plans was found for the lung, pediatric brain, and HNC cases, where compared to the VMAT plans normal organ doses were reduced by up to 22%, 75%, and 75%, respectively, with further reductions in mean doses seen in the 200 MeV plans. Previous studies investigating VHEE plans in radiation oncology have shown similar reductions in OAR doses . However, for the prostate case, a reduction in OAR dose for the 100 MeV VHEE plan could not be found, and the plan showed highest doses for bladder, rectum, and urethra among the four plans.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The largest benefit for the 100 MeV VHEE plans was found for the lung, pediatric brain, and HNC cases, where compared to the VMAT plans normal organ doses were reduced by up to 22%, 75%, and 75%, respectively, with further reductions in mean doses seen in the 200 MeV plans. Previous studies investigating VHEE plans in radiation oncology have shown similar reductions in OAR doses . However, for the prostate case, a reduction in OAR dose for the 100 MeV VHEE plan could not be found, and the plan showed highest doses for bladder, rectum, and urethra among the four plans.…”
Section: Discussionmentioning
confidence: 68%
“…The generation of the VHEE beams has been described elsewhere . Briefly, the VHEE pencil beams were calculated in the Monte Carlo EGSnrc/DOSXYZnrc code for 100 and 200 MeV beams through an in‐house developed graphical user interface in Matlab (The Mathworks, Nattick, MA, USA), which has been previously described . The beamlet doses were imported into RayStation and used for dose computation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies have shown that irradiations using a high dose‐per‐pulse electron beam with a high dose rate can increase the differential response between normal and tumor tissue compared to radiotherapy delivered with conventional dose rates (of a few Gy/min) . Extremely fast irradiations may also improve motion management issues, since the treatment could be delivered to the patient more rapidly than the timeframe of physiological motions . These investigations raised the challenge of performing reliable dosimetry in unusual irradiation conditions, such as those produced by a prototype high dose‐per‐pulse linac recently installed in our department.…”
Section: Introductionmentioning
confidence: 99%